2007
DOI: 10.1159/000101853
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study on the Effects of Nadroparin-Based and Citrate-Based Continuous Venovenous Hemofiltration on Calcium Metabolism

Abstract: Backgrounds: To study calcium homeostasis during citrate-based compared to nadroparin-based CVVH in critically-ill patients with acute renal failure. Methods: 11 patients were observed during citrate anticoagulation, 9 with nadroparin and 10 controls. Citrate was chosen for patients with active or at risk for bleeding. Results: The controls had, at 24 h, a median serum iCa of 1.1 mmol/l, the citrate group 0.87 mmol/l and the nadroparin group 1.1 mmol/l (citrate vs. control p = 0.001, citrate vs. nadroparin p =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 22 publications
(18 reference statements)
5
20
1
Order By: Relevance
“…Like Van der Voort et al [14], we found that the median PTH values were already above the normal range at baseline and rose further in the first 12-24 h before falling again. The average PTH levels were always above the normal range.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Like Van der Voort et al [14], we found that the median PTH values were already above the normal range at baseline and rose further in the first 12-24 h before falling again. The average PTH levels were always above the normal range.…”
Section: Discussionsupporting
confidence: 85%
“…Serum calcium levels are restored by calcium supplementation and calcium release upon citrate metabolism. Some protocols allow mild systemic hypocalcaemia to occur provided clinical signs of hypocalcaemia are absent [14,15,20]. Low serum [Ca i ] is the main physiologic trigger for PTH release.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations